Траектория: [повесть] / Александр Ярушкин, Леонид Шувалов - Ярушкин Александр Григорьевич (Сибирский приключенческий роман, 2016)
Экземпляры: ф.6 (20190719) / Инвентарный номер: 3357 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Я 78 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44